Response: Retaking the Archive of Knowledge about Solitary Confinement - Reiter, Keramet (Social justice, 2016)
The author responds to discussions of his book "23/7: Pelican Bay Prison & the Rise of Long-Term Solitary Confinement." Topics considered include National U.S. policies towards prisons, incarceration, and the administration of criminal justice; prison reform; the California Department of Corrections and Rehabilitation; and the practice of solitary confinement.